Ferroptosis as a Novel Therapeutic Target for Diabetes and Its Complications - Yang, Xi-Ding; Yang, Yong-Yu (Frontiers in Endocrinology, 2022)
The global diabetes epidemic and its complications are increasing, thereby posing a major threat to public health. A comprehensive understanding of diabetes mellitus (DM) and its complications is necessary for the development of effective treatments. Ferroptosis is a newly identified form of programmed cell death caused by the production of reactive oxygen species and an imbalance in iron homeostasis. Increasing evidence suggests that ferroptosis plays a pivotal role in the pathogenesis of diabetes and diabetes-related complications. In this review, we summarize the potential impact and regulatory mechanisms of ferroptosis on diabetes and its complications, as well as inhibitors of ferroptosis in diabetes and diabetic complications. Therefore, understanding the regulatory mechanisms of ferroptosis and developing drugs or agents that target ferroptosis may provide new treatment strategies for patients with diabetes.